The NPs Role of Assessing and Intervening with Older Adult Drivers - Tamatha Arms (Nursing Research and Practice)
As the silver tsunami continues, assessing and intervening with older adult drivers are becoming an essential aspect of the comprehensive geriatric exam. The current lack of time efficient clinical guidelines is a concern and barrier for NPs. The purpose of this study was to identify strategies currently used by NPs. The critical incident technique was used to obtain data from a convenience sample of NPs. A total of 89 incidents were collected. The perspective of the NP can provide important information for developing clinical guidelines to promote individual and community safety.